Clinical and Radiological Resolution of Grade-III Knee Osteoarthritis through Panchakarma: A Case Report - Sutagatti, Kavita Balagouda; Gramapurohit, Pradeep Laxman (Asian Journal of Biological and Life Sciences, 2025)
Knee Osteoarthritis (KOA), commonly referred to as degenerative joint disease, generally arises from the gradual deterioration and progressive depletion of articular cartilage. Conventional treatment including NSAID’s and surgical options which makes patients to turn to explore ayurveda treatments. In Ayurveda KneeOsteoarthritis (KOA) is understood as Janu Sandhigata Vata, resulting from imbalance in vata and kapha. A 64-year-old patient reported experiencing pain in both knees after surgical correction advise by conventional medicine. She had Knee pain score (VAS) 8, bulge test- positive, knee flexion- 60° with pain and marked reduced knee joint space with cartilage damage, subchondral sclerosis and osteophytes. Clinical and Radiological resolution of Grade III knee Osteoarthritis through panchakarma therapies, oral formulations and knee exercises. This prospective case study examined a diagnosed Grade III Knee Osteoarthritis (KOA) patient underwent a one year of treatment. The protocol included Panchakarma therapies (Upanaha, Janu Basti, Panchatikta Basti and Abhyanga Patra Pinda sweda) and Ayurvedic oral medications along with knee exercises. The Visual Analog Scale (VAS), Knee Range of Movements, WHOQOL-BREF Scale were assessed every 90 days over one year. Knee X-Ray was taken after a year. Patient showed satisfactory outcomes without any adverse effects. The Visual Analog Scale improved from 8 to 2, and significant changes were noted in the WHOQOL-BREF Scale along with the range of motion (flexion increased from 60° to 110° in both limbs) and a negative bulge test. Consistent and satisfactory improvements were observed after each follow-up, later after one year, X-ray showed increased knee joint space and reduced subchondral sclerosis. This study provides evidence that Upanaha, Janu Basti, Panchatikta Basti and Abhyanga Patra Pinda sweda over a year of period may successfully resolve Janu Sandhi Gata Vata (Grade-III Knee Osteoarthritis).
Keywords: Knee osteoarthritis; Panchakarma; Case report